An Important Reminder: Structuring a Classroom Environment That Honours All Students (LEARNing Landscapes, 2014)
All children, regardless of ability, should feel valued and respected in their classroom. At times, the children who struggle miss out on purpose-driven, meaningful learning because they are classified by what they cannot do instead of honoured for what they can do. Through my narrative of Henry, I explore the importance of truly coming to know each student as a learner in the classroom. I begin by reflecting on my own experiences in school as a student and then as a beginning teacher. I then explore the use of the reader’s workshop model and discuss how I have used it as an approach to differentiated teaching and learning in a way that creates space for relationships to grow and students to be supported. Finally, I conclude by revisiting my story of Henry and reflect on how his story, and implementing the reader’s workshop model, will continue to affect my teaching as I grow both as a teacher and learner.
Keywords: narrative; learner; student; inclusion; reader’s workshop model; support; teacher; teaching